2007
DOI: 10.1001/archpedi.161.10.978
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplement Use Among Infants, Children, and Adolescents in the United States, 1999-2002

Abstract: Objective: To describe dietary supplement use among US children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
124
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(157 citation statements)
references
References 36 publications
27
124
6
Order By: Relevance
“…Canadian and American youth averages of respectively 23% and 25% [158,159]. The discrepancy in regard to total dietary intake of vitamin D in this population compared to national averages is thus most likely attributable to the increased awareness of the importance of consuming daily dietary vitamin D sources in patients with a bone fragility disorder such as OI.…”
Section: Discussionmentioning
confidence: 94%
“…Canadian and American youth averages of respectively 23% and 25% [158,159]. The discrepancy in regard to total dietary intake of vitamin D in this population compared to national averages is thus most likely attributable to the increased awareness of the importance of consuming daily dietary vitamin D sources in patients with a bone fragility disorder such as OI.…”
Section: Discussionmentioning
confidence: 94%
“…Feeding-practice categories are mutually exclusive and based only on consumption of breast milk and formula. 19 Pediatricians and allied health care providers are uniquely positioned to help increase the percentage of infants who receive adequate amounts of vitamin D, because parents are more likely to give their children vitamin D supplements if they are advised to do so by a health care professional. 20 It is unfortunate that many health care professionals are not recommending vitamin D supplements for infants.…”
Section: Resultsmentioning
confidence: 99%
“…The 1988-1994 National Health and Nutrition Survey (NHANES) found that 23?9 % of US adolescents (age 12-19 years) used supplements (7) . Further studies based on the 1999-2004 NHANES reported similar rates (age 9-19 years; 26-29 %) (6,8,9) . Two studies differentiated between younger and older adolescents (6,8) and found conflicting results.…”
mentioning
confidence: 80%